Nilai-Nilai Pendidikan Multikultural Pada Budaya Sakai Sambayan Dalam Menumbuh Kembangkan Sikap Toleransi Masyarakat Lampung Pepadun - Evan, Evan Supriyadi; Rahmat (Academicus: Journal of Teaching and Learning, 2023)
The value of education with a multicultural perspective contained in the Sakai Sambayan culture, is used as a reference to develop the norms of life for the people of Lampung Pepadun in educating the nation's character and creating an attitude of tolerance. This is because of the rapid development of social media or mass media which is almost felt by all groups by providing its own pampering and having an effect on the emergence of a negative culture, lifestyle, individualistic attitude, and a low sense of help. So the Sakai Sambayan culture must be instilled in the minds of every community to form a society that is social and tolerant. This study shows that the values ​​of multicultural education in the Sakai Sambayan culture in developing a tolerance attitude of the people of Lampung Pepadun are: 1) Can increase a sense of unity and integrity, 2) Can strengthen brotherhood ties, 3) Able to create voluntary attitudes, help, and togetherness among community members, 4) Able to ease and accelerate work in the community, and 5) Establish and maintain social relations and harmony among community members. The implications or application of the Sakai Sambayan culture in developing the tolerance attitude of the people of Lampung Pepadun are with the following activities: 1) Hioh sumbay activities, 2) Deliberations to reach consensus, 3) Mutual cooperation activities in the agricultural sector, 4) Activities at weddings, and 5) Activities community (building places of worship and cleaning Tiyuh).